2007
DOI: 10.1016/j.jacc.2006.10.065
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Coronary In-Stent Restenosis Using 64-Slice Computed Tomography

Abstract: ObjectivesThis study sought to evaluate the diagnostic accuracy of coronary binary in-stent restenosis (ISR) with angiography using 64-slice multislice computed tomography coronary angiography (CTCA) compared with invasive coronary angiography (ICA).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(45 citation statements)
references
References 37 publications
2
40
0
3
Order By: Relevance
“…However, the visualisation of stent lumen and the quantification of lumen narrowing by neointimal hyperplasia with CT were hindered by blooming artefacts caused by the metallic stent struts. The studies performed with 64-slice CT showed a significant improvement for ISR detection in comparison with previous generation systems, because of the higher spatial and temporal resolution [4][5][6]. However, the radiation burden (10-20 mSv) of 64-slice CT reported in these studies is still a drawback [4][5][6].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, the visualisation of stent lumen and the quantification of lumen narrowing by neointimal hyperplasia with CT were hindered by blooming artefacts caused by the metallic stent struts. The studies performed with 64-slice CT showed a significant improvement for ISR detection in comparison with previous generation systems, because of the higher spatial and temporal resolution [4][5][6]. However, the radiation burden (10-20 mSv) of 64-slice CT reported in these studies is still a drawback [4][5][6].…”
Section: Introductionmentioning
confidence: 91%
“…The studies performed with 64-slice CT showed a significant improvement for ISR detection in comparison with previous generation systems, because of the higher spatial and temporal resolution [4][5][6]. However, the radiation burden (10-20 mSv) of 64-slice CT reported in these studies is still a drawback [4][5][6]. In recent years, different strategies have been introduced into clinical practice, aimed at improving diagnostic performance and reducing radiation dose, including optimisation of imaging parameters [7], introduction of dual-source CT [8,9], increase in the number of slices [10,11] and high-pitch scanning [12], obtaining controversial results.…”
Section: Introductionmentioning
confidence: 99%
“…As Diretrizes da Sociedade Brasileira de Cardiologia consideram a indicação dessa técnica no diagnóstico das anomalias coronárias como classe 1 e classe 2 para avaliação de estenose nessas artérias em pacientes com baixa probabilidade de doença arterial coronária e testes não-invasivos inconclusivos. Outras indicações, como estudo das pontes de safena, 5 de stents 6 ou de pacientes com média ou mesmo alta probabilidade de estenose grave de artérias coronárias, encontram-se em fase de validação. 7 Apesar da expansão do uso da angiotomografia coronária com múltiplos detectores no arsenal diagnóstico para avaliação da cardiopatia isquêmica, ainda não existem estudos analisando sua utilização em pacientes da prática clínica diária, o chamado mundo real.…”
Section: Multidetector Computed Tomographic Angiography Of Coronary Aunclassified
“…Stents de pequeno calibre, calcificações adjacentes e artefatos de movimento prejudicam a avaliação dos stents. 6,20 O estudo de pontes de safena e de enxertos arteriais com a angiotomografia coronária com múltiplos detectores é favorecido pela menor mobilidade e pelo maior calibre dessas estruturas. Comparando com a cinecoronariografia por cateter, Meyer et al 5 estudaram 397 pacientes utilizando tomografia computadorizada com 64 detectores, encontrando 100% de sensibilidade e 92% de especificidade.…”
Section: Número De % Pacientesunclassified
“…The aim of these studies in the beginning was to investigate the stent expansion process, [32] afterwards to define the "stent lumen visibility" at in vitro conditions [33] or after the insertion of the stent [34,35,36,37,38]. CT scans were valued on a four or five-degree scale from "excellent" to "not gradable", etc.…”
Section: Introductionmentioning
confidence: 99%